LITERASI INFORMASI PERTANIAN OLEH KOMUNITAS PERTANIAN PERKOTAAN DI LABORATORIUM PERPUSTAKAAN PERTANIAN BERBASIS INKLUSI SOSIAL - Herwan Junaidi (Perpustakaan Nasional RI, 2022)
Libraries have a major contribution in building a knowledge society through collective efforts, to foster reading traditions and culture in society. The purpose of this research is to determine the role of agricultural information literacy by the community and the agricultural community in the Agricultural Library Laboratory Based on Social Inclusion. This study uses a qualitative descriptive method with an experimental method. The activity was carried out in March-June 2020 at the Urban Agricultural Community (KPP) or KWT which utilizes the agricultural library laboratory as a source of information in optimizing the yard. The number of KWT community members who were sampled were 45 people. The study was conducted in RW.005 Babakan Lebak, Balumbang Jaya Village, Dramaga District - West Bogor. The Agricultural Library Laboratory has provided benefits to the surrounding community. In addition to providing a collection of reading materials and agricultural teaching aids, LPP also facilitates the community in various activities and needs including a cow working space (CWS), angklung playing facilities, martial arts facilities, dance training, teaching and learning exercises and others. Urban agricultural communities/Women Farmers Groups make LPP a vehicle for community activities in searching for literature to support knowledge and understanding in farming. The number of residents registered in urban agricultural activities is 45 people. The average age of KWT members is 44 years.